Development and Characterization of Solid Lipid Nanoparticles Loaded with a Highly Active Doxorubicin Derivative - Barbara Stella (Nanomaterials, 2018)
Solid lipid nanoparticles (SLNs) comprise a versatile drug delivery system that has been developed for the treatment of a variety of diseases. The present study will investigate the feasibility of entrapping an active doxorubicin prodrug (a squalenoyl-derivative) in SLNs. The doxorubicin derivative-loaded SLNs are spherically shaped, have a mean diameter of 300–400 nm and show 85% w/w drug entrapment efficiency. The effects on cell growth of loaded SLNs, free doxorubicin and the prodrug have been examined using cytotoxicity and colony-forming assays in both human ovarian cancer line A2780 wild-type and doxorubicin-resistant cells. Further assessments as to the treatment’s ability to induce cell death by apoptosis have been carried out by analyzing annexin-V staining and the activation of caspase-3. The in vitro data demonstrate that the delivery of the squalenoyl-doxorubicin derivative by SLNs increases its cytotoxic activity, as well as its apoptosis effect. This effect was particularly evident in doxorubicin-resistant cells.